PKCθ/β and CYLD are antagonistic partners in the NFκB and NFAT transactivation pathways in primary mouse CD3+ T lymphocytes. - Nikolaus Thuille; Katarzyna Wachowicz; Natascha Hermann-Kleiter; Sandra Kaminski; Friedrich Fresser; Christina Lutz-Nicoladoni; Michael Leitges; Margot Thome; Ramin Massoumi; Gottfried Baier (PLoS ONE, 2013)
In T cells PKCθ mediates the activation of critical signals downstream of TCR/CD28 stimulation. We investigated the molecular mechanisms by which PKCθ regulates NFκB transactivation by examining PKCθ/β single and double knockout mice and observed a redundant involvement of PKCθ and PKCβ in this signaling pathway. Mechanistically, we define a PKCθ-CYLD protein complex and an interaction between the positive PKCθ/β and the negative CYLD signaling pathways that both converge at the level of TAK1/IKK/I-κBα/NFκB and NFAT transactivation. In Jurkat leukemic T cells, CYLD is endoproteolytically processed in the initial minutes of stimulation by the paracaspase MALT1 in a PKC-dependent fashion, which is required for robust IL-2 transcription. However, in primary T cells, CYLD processing occurs with different kinetics and an altered dependence on PKC. The formation of a direct PKCθ/CYLD complex appears to regulate the short-term spatial distribution of CYLD, subsequently affecting NFκB and NFAT repressional activity of CYLD prior to its MALT1-dependent inactivation. Taken together, our study establishes CYLD as a new and critical PKCθ interactor in T cells and reveals that antagonistic PKCθ/β-CYLD crosstalk is crucial for the adjustment of immune thresholds in primary mouse CD3(+) T cells.